Effects of soil management systems on soil microbial activity, bulk density and chemical properties - Valpassos, Maria Alexandra Reis; Cavalcante, Eloiza Gomes Silva; Cassiolato, Ana Maria Rodrigues; Alves, Marlene Cristina (Pesquisa Agropecuaria Brasileira, 2001)
The objective of this experiment was to study the effects of soil management systems on the bulk density, chemical soil properties, and on the soil microbial activity on a Latossolo Vermelho distrófico (Oxisol). Soil samples were collected from plots under the following management conditions: a) natural dense "cerrado" vegetation (savanna); b) degraded Brachiaria decumbens pasture, 20 years old; c) no-tillage treatment with annual crop sequence (bean, corn, soybean and dark-oat in continuous rotation), 8 years old; d) conventional tillage treatment with crop residues added to the soil, and annual crop sequence, 10 years old. The continuous use of no-tillage system resulted in an increase in microbial biomass and decrease in soil basal respiration, therefore displaying evident long-term effects on the increase of soil C content. The no-tillage system also provided an improvement in bulk density and chemical properties of the soil. Hence, the no-tillage management system could be an alternative for the conservation and maintenance of physical and chemical conditions and the productive potential of "cerrado" soils.